Concentration of carbon dioxide in ventilated rooms - Kapalo, Peter; Pauliková, Alena (Видавництво Львівської політехніки, 2012)
Сьогодні існує глобальна тенденція до будівництва будівель, які класифіковані як низькоенергетичні будинки з теплотехнічного боку. Відповідно до природної вентиляції вони називаються жорсткі будинки. Обмін повітря за допомогою природної вентиляції в такому вигляді будівель знижується нижче необхідних значень згідно з гігієнічними нормами. З метою забезпечення необхідного повітрообміну потрібно встановити в цих будівлях примусову чи гібридну вентиляції. On the present there is a global trend to construct buildings which are categorized like low-energy houses with regard to the thermal-technical viewpoint. According to the natural ventilation they are called tight buildings. An exchange of the air by means of natural ventilation in such kind of buildings is reduced below the hygienically required limit.In rder to ensure the required air exchange it is necessary to install into these buildings the forced or hybrid ventilation.
Keywords: двоокис вуглецю; температура повітря; природна вентиляція; carbon dioxide; air temperature; natural ventilation